Into the cosmos : space exploration and Soviet culture - Siddiqi, Asif A., 1966-; Andrews, James T., 1961- (Series in Russian and East European studies., 2011)
"Into the Cosmos shows us the fascinating interplay of Soviet politics, science, and culture during the Khrushchev era, and how the space program became a binding force between these elements."--Back cover